The essential guide to intermittent fasting for women : balance your hormones to lose weight, lower stress, and optimize health - Ramos, Megan (Greystone Books, 2023)
"Struggling with your metabolism and hormone health? Disappointed by diets that don't provide sustainable, long term results? Sick of feeling tired and stressed all the time? Megan Ramos was in the same position when she discovered intermittent fasting at the clinic where she was a researcher. After suffering from non-alcoholic fatty liver disease, PCOS, and type 2 diabetes, she harnessed the power of fasting to reverse these conditions, lose over 80 pounds, and achieve long-lasting health. Today, as the co-founder of The Fasting Method with Dr. Jason Fung, she has helped over 20,000 people, primarily women, improve their wellbeing through intermittent fasting. In The Essential Guide to Intermittent Fasting for Women, Ramos shares: - Easy-to-use fasting protocols that can be incorporated into your busy schedule - Information on when and how to eat to feel full and energized - How intermittent fasting can support your health through fertility struggles, PCOS, perimenopause, and menopause - How balancing your hormones and stress levels can help you avoid weight gain and depression. Designed specifically for women of all ages and their unique needs, this go-to guide provides you with the steps to take control of your health--for good."--Amazon.com.